2017
DOI: 10.1001/jamacardio.2017.1413
|View full text |Cite
|
Sign up to set email alerts
|

Association of Implantable Cardioverter Defibrillators With Survival in Patients With and Without Improved Ejection Fraction

Abstract: clinicaltrials.gov Identifier: NCT01114269.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 44 publications
4
51
1
Order By: Relevance
“…Compared with placebo, the adjusted HR for the effect of ICD on mortality was 0.64 (95% CI 0.48 to 0.85) in patients with a repeated EF of ≤35% and 0.62 (95% CI 0.29 to 1.30) in those with a repeated EF >35%. These data suggest that patients who had an improvement in EF >35% during follow-up accrued a similar mortality benefit with ICD as those whose EF remained ≤35% 18. Similar findings were reported in other smaller studies where improvement in EF >35% was associated with lower risk of ICD therapies; however, the residual arrhythmic risk was significant enough to warrant ongoing ICD therapy 9 11 12.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Compared with placebo, the adjusted HR for the effect of ICD on mortality was 0.64 (95% CI 0.48 to 0.85) in patients with a repeated EF of ≤35% and 0.62 (95% CI 0.29 to 1.30) in those with a repeated EF >35%. These data suggest that patients who had an improvement in EF >35% during follow-up accrued a similar mortality benefit with ICD as those whose EF remained ≤35% 18. Similar findings were reported in other smaller studies where improvement in EF >35% was associated with lower risk of ICD therapies; however, the residual arrhythmic risk was significant enough to warrant ongoing ICD therapy 9 11 12.…”
supporting
confidence: 81%
“…In the Sudden Cardiac Death in Heart Failure Trial substudy, 1273 patients with reduced EF ≤35% assigned to ICD versus placebo were analysed 18. During a median follow-up of 30 months, EF improved to >35% in about 30% of patients in each group.…”
mentioning
confidence: 99%
“…13,14 In a study of 195 patients, 50 (25.6%) had 10% improvement in LVEF reaching a median LVEF during follow-up of 41% (25th, 75th percentiles 37%, 49%). 15 Studies have shown that LVEF improvement is associated with a significant long-term reduction in heart failure hospitalizations, ICD shocks, and death.…”
Section: Data On Icdsmentioning
confidence: 99%
“…The mean LVEF at the most recent follow‐up was >35% (Table 1), most likely because of (1) inclusion of cases where LVEF does not need to be low at the time of ICD implantation (arrhythmogenic right ventricular cardiomyopathy [ARVC], cardiac sarcoidosis, inherited arrhythmia syndromes, etc. ), and (2) improvement in LVEF that occurs in 25%–50% of patients after ICD implantation 22–28 …”
Section: Discussionmentioning
confidence: 99%